A network in the shape of a wheel of outer vertices is assembled such that every branch of the wheel consists of a resistor. Let denote the effective resistance between two outer adjacent nodes of the network. Evaluate the expression for in terms of , and then find .
If the limit is equal to for coprime integers , submit .
Note: To visualize the network topology, see Wheel Graph .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Suppose that current I enters the circuit at vertex 1 , and leaves at vertex n . Let the potentials at vertices 1 , 2 , ..., n be V 1 , V 2 , ..., V n . Let the current from vertex k to vertex k + 1 be I k for 1 ≤ k ≤ n − 1 , and let the current from vertex n to vertex 1 be I n . Let the potential at the central vertex be 0 , and let the current from the central vertex to vertex k be J k for 1 ≤ k ≤ n .
Since current is neither created nor destroyed we deduce that I 1 − I n − J 1 I k − I k − 1 − J k I n − I n − 1 − J n = I = 0 2 ≤ k ≤ n − 1 = − I so that J k = ⎩ ⎨ ⎧ I 1 − I n − I I k − I k − 1 I n − I n − 1 + I k = 1 2 ≤ k ≤ n − 1 k = n and we also have J k R = − V k 1 ≤ k ≤ n I k R = { V k − V k + 1 V n − V 1 1 ≤ k ≤ n − 1 k = n Combining these equations we deduce that V k + 1 − 3 V k + V k − 1 = 0 2 ≤ k ≤ n − 1 and hence we deduce that V k = A α k + B α − k 1 ≤ k ≤ n where α = 2 1 ( 3 + 5 ) . Satisfying the boundary conditions gives us that A = ( α − α − 1 ) ( 1 − α n ) I R ( 1 − α − 1 ) B = ( α − α − 1 ) ( 1 − α − n ) I R ( α − 1 ) and so the effective resistance of the circuit is R n = I V 1 − V n = R [ ( α − α − 1 ) ( 1 − α n ) ( 1 − α − 1 ) ( α − α n ) + ( α − α − 1 ) ( 1 − α − n ) ( α − 1 ) ( α − 1 − α − n ) ] and hence n → ∞ lim R n = R [ α − α − 1 1 − α − 1 + α − α − 1 ( α − 1 ) α − 1 ] = α − α − 1 2 ( 1 − α − 1 ) = 1 − 5 1 making the answer 1 + ( − 1 ) + 5 = 5 .